Effects of Moringa oleifera supplementation on immune and nutritional biomarkers in adults living with HIV: a systematic review and meta-analysis - Jin, Dachuan; Jin, Shunqin; Zhou, Tao; Sheng, Guoping; Gao, Peng; Li, Guangming (Frontiers in Nutrition, 2025)
BackgroundMoringa oleifera (MO) is widely used as an adjunctive therapy for individuals living with HIV (PLWH) due to its nutritional and immune-modulating properties.ObjectiveTo systematically evaluate the effects of MO supplementation on immune and nutritional indicators in Human Immunodeficiency Virus (HIV)-infected adults.MethodsWe conducted a systematic review and meta-analysis by searching PubMed, EmBase, Web of Science, and Cochrane Library to include studies assessing the impact of MO supplementation on immune and nutritional markers, such as CD4+ T cell count, BMI, white blood cell (WBC) count, and platelet (PLT) count in PLWH. Data were pooled using random-effects or fixed-effects models, and subgroup and meta-regression analyses were performed to assess sources of heterogeneity.ResultsA total of seven articles (eight study datasets) were included. MO supplementation significantly increased CD4+ T cell count [standardized mean differences (SMD) = 1.4, 95% CI 0.59–2.20, p < 0.001], WBC (SMD = 0.22, 95% CI 0.02–0.42, p = 0.030), and PLT count (SMD = 3.14, 95% CI 2.37–3.92, p < 0.001), with a significant improvement in BMI (SMD = 0.29, 95% CI 0.03–0.55, p = 0.028). Subgroup analysis demonstrated consistent effects in both randomized controlled trials (RCTs) and non-RCTs, while meta-regression indicated that dosage influences outcomes (p = 0.007). Further studies with larger sample sizes are warranted.ConclusionsMO supplementation significantly improves immune function and nutritional status in PLWH. Further high-quality studies are needed to confirm its efficacy and safety.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251000927, PROSPERO: CRD420251000927.